A Comparative Study on Interpretation of Planet from Al-Quran and Astronomy Views - Wahid, Khairussaadah; Nawawi, Mohd Saiful Anwar Mohd; Man, Saadan (Brill Academic Publishers, 2017)
The interpretation submitted by the translator of mashaf Quran against the pronouncement of al-kawkab and al-kawakib means 'star'. Based on the studies from the modern astronomy, both words refer to a planet. The study of the meaning of al-kawkab and al-kawakib is about explaining more appropriate meanings based on the context of Islamic astronomy. The main objective of this study is to identify the meaning of al-kawkab and al-kawakib terms in al-Quran and to analyze the correlation between Quranic commentaries with modern discoveries of planets in the solar system. Methods of comparison between the views of Quranic commentaries and modern astronomy are highlighted with reference based on classical and contemporary tafseers, and modern astronomy literature. The study found that there are four passages that discuss physical characteristics of planets. In addition, the reason that may be adduced to explain appropriate translations for the words al-kawkab and al-kawakib as 'planet' is based on the majority of Quranic commentaries and research on the difference in physical nature of planets and stars. In conclusion, the is no difference between Quranic commentaries and modern astronomy related to planets and their features. Thus the pronouncement of al-kawkab and al-kawakib in the Quran refers to a planet, not a star.